Assessing Environmental Quality Using the Risk Screening Environmental Indicators (RSEI) Method: A Multi-Year Remote Sensing Approach - Wahid Akhsin Budi Nur Sidiq; Tjaturahono Budi Sanjoto; Abdul Jabbar (Advance Sustainable Science Engineering and Technology, 2025)
Industrial areas in Indonesia are increasing every year with a total of 136 industrial estates in 2024, of which 61.76% are in Java, such as Kendal Industrial Estate (KIE) with an increase in built-up land of 289.52 hectares (2015-2017). The problem is that the development was carried out by converting vegetation cover. The purpose of the study was to analyze the impact of the increase in built-up land on the environmental quality index around Kendal Industrial Estate. Research method with supervised classification Random Forest method and spectral transformation Risk Screening Enviromental Indicators with indicators of greenness index, humidity Index, dryness Index and heat index with Principal Component Analysis technique. The results showed that built-up land around KIE increased by 894.17 hectares which resulted in a decrease in vegetation cover of 184.71 hectares (2015-2024), this phenomenon had an impact on increasing low-level RSEI by around 2,028.31 hectares (2015-2024). The regression results show that the increase in built-up land and the reduction of vegetation cover have an impact on the decline in environmental quality in the study area. The contribution of the research results can be used as a database for regulation of land use change restrictions.